2019
DOI: 10.1002/adfm.201900881
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Formation of Gold Halides in Single‐Crystal Hybrid‐Perovskite/Au Interface upon Biasing and Effect on Electronic Carrier Injection

Abstract: Solar cells, light emitting diodes, and X-ray detectors based on perovskite materials often incorporate gold electrodes, either in direct or indirect contact with the perovskite compound. Chemical interactions between active layers and contacts deteriorate the operation and induce degradation, being the identification of the chemical nature of such interfacial structures an open question. Chemical reactivity of gold in contact with the perovskite semiconductor leads to reversible formation of oxidized gold hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 33 publications
(45 reference statements)
3
60
0
Order By: Relevance
“…Birkhold et al previously reported ionic charging and PL quenching near electrodes on comparable timescales which indicates that slow poling fields are likely to influence the defect densities in MAPbI 3 due to ionic movement . Other reports described similar ionic charge build‐up or even chemical interaction of ionic species with the electrode interface at high voltages …”
Section: Origin Of Poling Effectsmentioning
confidence: 62%
“…Birkhold et al previously reported ionic charging and PL quenching near electrodes on comparable timescales which indicates that slow poling fields are likely to influence the defect densities in MAPbI 3 due to ionic movement . Other reports described similar ionic charge build‐up or even chemical interaction of ionic species with the electrode interface at high voltages …”
Section: Origin Of Poling Effectsmentioning
confidence: 62%
“…In order to solve this problem in single crystalline hybrid perovskites, studies have shown that certain interfaces can cause hysteretic behavior due to interfacial recombination, low interfacial resistance, and chemical reactions at the interface forming metal‐halide compounds between the semiconductor and electrode. [ 31,44 ] In the single crystal devices, similar issue may also exist. Therefore, we characterize the current–voltage curves and instability through monitoring hysteresis as a function of long‐term, high voltage biasing on our detector in dark as summarized in Figure .…”
Section: Resultsmentioning
confidence: 98%
“…In previous reports, it has been shown that Br − atoms can form complexes with metals such as Au. [ 44 ] However, this was found to be a reversible formation at low biases, important for optoelectronic processes, where the Cr/MAPbBr 3 interface did not show signs of hysteresis at lower voltages. [ 31 ] For high‐energy γ‐ray detection, where single photon induced pulses need to be collected, high electric fields are required for optimized charge collection efficiency and reduction of trapping to ensure high resolution signal.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14,18,23 ] In particular, the accumulation and reaction of the ions with the Au electrode could further result in deterioration of the perovskite layer [ 16,29,31 ] under long‐term operation and aggravate the decay of EL efficiency and thus EQE. We also note that the driving voltage for keeping the constant current density is decreased during operation (Figure 1c), this might be related to the modification of carrier injection barrier [ 32 ] or formation of leakage paths after I − migration and metal‐halide reaction.…”
Section: Figurementioning
confidence: 99%